Assessment of Some Physicochemical Parameters and Heavy Metals in Hand-Dug Well Water Samples of Kafta Humera Woreda, Tigray, Ethiopia - Kiros Gebremichail Gebresilasie; Goitom Gebreyohannes Berhe; Amanual Hadera Tesfay; Samuel Estifanos Gebre (International Journal of Analytical Chemistry)
Groundwater is one of the most important sources of drinking water in Kafta Humera Woreda; hence, it is important to assess the quality of these water sources. The aim of this study was to assess the levels of some physicochemical parameters and heavy metals in hand-dug well water sources of Kafta Humera Woreda. The results showed that the physicochemical concentrations of the hand-dug well water samples were given as follows: temperature, 27.67 ± 0.15 to 28.30 ± 0.25°C; pH, 6.90 ± 0.33 to 8.20 ± 0.36; dissolved oxygen, 5.60 ± 0.06 to 6.2 ± 0.04 mg/L; turbidity, 1.67 ± 0.02 to 1.89 ± 0.03 NTU; EC, 148.50 ± 0.89 to 932.00 ± 0.98 μS/cm; TDS, 105.80 ± 0.62 to 664.28 ± 0.70 mg/L; total hardness, 71.80 ± 3.05 to 295.30 ± 2.38 mg/L; total alkalinity, 75 ± 5.0 to 215 ± 5.0 mg/L; calcium, 12.02 ± 0.82 to 75.88 ± 0.93 mg/L; magnesium, 9.80 ± 0.80 to 25.70 ± 0.17 mg/L; potassium, 0.130 ± 0.003 to 0.86 ± 0.04 mg/L; sodium, 2.20 ± 0.16 to 12.75 ± 0.87 mg/L; chloride, 12.86 ± 0.02 to 42.72 ± 0.20 mg/L; sulfate, 17.24 ± 0.96 to 118.67 ± 0.46 mg/L; phosphate, 0.018 ± 0.005 to 0.020 ± 0.002 mg/L; and nitrate, 1.86 ± 0.03 to 5.43 ± 0.06 mg/L. Generally, the concentrations of most physicochemical parameters of the hand-dug well water samples of Kafta Humera Woreda were within the permissible limit of World Health Organization and Ethiopian Standard Agency guideline for drinking water. The statistical Pearson’s correlation analysis on the water quality parameters revealed that all parameters are more or less correlated with each other. Electrical conductivity and total dissolved solids of the water samples were found to be significantly correlated with total hardness (r = 0.989), total alkalinity (r = 0.827), calcium (r = 0.988), magnesium (r = 0.881), sodium (r = 0.995), potassium(r = 0.996), chloride (r = 0.998), sulfate (r = 1), and nitrate ions (r = 0.972). Out of the selected seven heavy metals, Fe, Cu, Zn, Mn, Cr, Cd, and Pb, only iron was detected in all water samples and its concentration was above the permissible limit of WHO and ESA for drinking water. Therefore, the government should adopt some treatment technologies such as sedimentation and aeration to minimize the concentration of iron for safe drinking the water to the community of Kafta Humera Woreda.